Supuración parahidática transdiafragmática por quiste hidático de hígado - Lizaso, Isabel; Torterolo, Edgardo; de Mattos, Alfredo; Medina, Raúl (Cirugía del Uruguay, 1980)
Unusual case of pulmonary supuration in a patient who was suffering from hydatid cyst in liver and attendant complications. Pathogenesis followed a transdiaphragmatic lymphatic route with absence of hepatopulmonary transit.